Effects of drought on thermal stability of photosynthetic apparatus in bread wheat and in Aegilops species originating from various habitats - Dulai, Sándor (Acta Biologica Szegediensis, 2005)
The responses of thermal stability of photosystem II to drought induced by dessication in soil pots were examined in two wheat (Triticum aestivum L.) cultivars and in Aegilops genotypes originating from habitats with different annual rainfalls and daily temperatures. The three days drought treatment did not effect a considerable water loss in leaves and parallel with this a significant heat-tolerance increase of PS II determined on the basis of breakpoints (Tc, Tp) of the temperature dependence of steady-state fluorescence level (Fs vs. T curves) at 1000 μE m-2 s-1 actinic light (AL) intensity was not observable. Higher water deficit (RWC<75%,10-14 day drought treatment) resulted in a significant increase in thermal stability, for wheat and for several Aegilops genotypes. In a dark-adapted state the critical values of the F0 vs. T curves did not shift towards significantly higher temperatures with an increase in water deficit. The results indicate that some Aegilops genotypes originating from arid habitats have better heat tolerance than wheat during drought, making them appropriate for improving the heat tolerance of wheat enabling it to survive the dry and hot periods in the field.